Experiences of persons with mobility impairment in using public transport in Knysna townships in the Western Cape Province - Gudwana, Khangelani (Stellenbosch : Stellenbosch University, 2020)
Thesis (MHumanRehabSt)--Stellenbosch University, 2020.